Organisational and Methodical Aspects of Drug and Addiction Prevention among Young People - Developments in the Ukraine, in Germany, Spain and Russia: a Project Description - Stephan Sting (Social Work & Society, 2003)
From october 2000 to march 2003 the project has been coordinated by the institute of social work and welfare studies of the TU Dresden and financed by the European Commission (INCO-COPERNICUS-Programme). It was an international cooperation between the TU Dresden (Germany), the University of Internal Affairs and the National Technical University in Kharkiv (Ukraine), the research institute AREA in Valenciá (Spain) and the Belgorod Juridical Institute of the Ministry of Internal Affairs (Russia) which was established for improving the knowledge base of drug prevention activities by the East European partners. The overall aim of the project was the analysis and elaboration of approaches to drug and addiction prevention. Under consideration of the specific conditions within the East-European countries this work should contribute to the development of pluralistic approaches towards health promotion which are embedded into an intercultural, European horizon.